Legal Mecanisms To Combat Illegal Immigration In Algeria - Farsi, Djamila (University of Eloued جامعة الوادي, 2022)
Algeria is overwhelmed by a flow of illegal migrants that has considerably grown in recent years, due to several factors, urging it to adopt a repressive legislative arsenal towards clandestine migrants by amending the Penal Code. This position has come in line with Algeria’s international obligations regarding the issue of illegal immigration, such as its ratification of the Protocol against the Smuggling of Migrants by Land, Sea and Air, besides the conclusion of bilateral agreements intended to resettling illegal immigrants. Despite this judicial arsenal, irregular immigration continues to escalate, calling for more suitable frameworks and effective solutions.الجزائر غارقة في تدفق المهاجرين غير الشرعيين الذي نما بشكل كبير في السنوات الأخيرة، بسبب عدة عوامل، تحثها على اعتماد ترسانة تشريعية قمعية تجاه المهاجرين السريين من خلال تعديل قانون العقوبات. ويأتي هذا الموقف في إطار الالتزامات الدولية للجزائر فيما يتعلق بمسألة الهجرة غير الشرعية، مثل تصديقها على بروتوكول مكافحة تهريب المهاجرين عن طريق البر والبحر والجو، إلى جانب إبرام اتفاقات ثنائية تهدف إلى إعادة توطين المهاجرين غير الشرعيين. وعلى الرغم من هذه الترسانة القضائية، تستمر الهجرة غير النظامية في التصاعد، مما يستدعي أطرا أكثر ملاءمة وحلولا فعالة.
مقال
Keywords: illegal Immigration ; International agrement ; European Union ; Security; الهجرة غير الشرعية ; التعددية الدولية ; الاتحاد الأوروبي; أمن